Light-mediated control of gene expression in the anoxygenic phototrophic bacterium Rhodobacter capsulatus using photocaged inducers - Hilgers, Fabienne; Hogenkamp, Fabian; Klaus, Oliver; Kruse, Luzie; Loeschcke, Anita; Bier, Claus; Binder, Dennis; Jaeger, Karl-Erich; Pietruszka, Jörg; Drepper, Thomas (Frontiers in Bioengineering and Biotechnology, 2022)
Photocaged inducer molecules, especially photocaged isopropyl-β-D-1-thiogalactopyranoside (cIPTG), are well-established optochemical tools for light-regulated gene expression and have been intensively applied in Escherichia coli and other bacteria including Corynebacterium glutamicum, Pseudomonas putida or Bacillus subtilis. In this study, we aimed to implement a light-mediated on-switch for target gene expression in the facultative anoxygenic phototroph Rhodobacter capsulatus by using different cIPTG variants under both phototrophic and non-phototrophic cultivation conditions. We could demonstrate that especially 6-nitropiperonyl-(NP)-cIPTG can be applied for light-mediated induction of target gene expression in this facultative phototrophic bacterium. Furthermore, we successfully applied the optochemical approach to induce the intrinsic carotenoid biosynthesis to showcase engineering of a cellular function. Photocaged IPTG thus represents a light-responsive tool, which offers various promising properties suitable for future applications in biology and biotechnology including automated multi-factorial control of cellular functions as well as optimization of production processes.